2018
DOI: 10.1111/bjh.15490
|View full text |Cite
|
Sign up to set email alerts
|

Myelodysplastic syndrome (MDS) with isolated trisomy 8: a type of MDS frequently associated with myeloproliferative features? A report by the Groupe Francophone des Myélodysplasies

Abstract: Isolated trisomy 8 (+8) is a frequent cytogenetic abnormality in the myelodysplastic syndromes (MDS), but its characteristics are poorly reported. We performed a retrospective study of 138 MDS patients with isolated +8, classified or reclassified as MDS (excluding MDS/myeloproliferative neoplasm). Myeloproliferative (MP) features were defined by the repeated presence of one of the following: white blood cell count >10 × 10 /l, myelemia (presence of circulating immature granulocytes with a predominance of more … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
13
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(17 citation statements)
references
References 33 publications
(36 reference statements)
4
13
0
Order By: Relevance
“…Conflicting data exist about the impact of trisomy 8 on OS of patients with MDS. Consistent with prior reports, 15,16,18,39 we found that patients with +8 had a markedly shorter OS in comparison with those who had NK (median survival 26.8 months vs. 47.5 months, p = 0.003). The analysis of Zoe et al included 496 MDS patients with karyotypic abnormalities from the Victorian Cancer Registry and showed that +8 was identified in 93 (18.75%) patients and independently predicted shorter OS in a multivariate analysis (p = 0.024).…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Conflicting data exist about the impact of trisomy 8 on OS of patients with MDS. Consistent with prior reports, 15,16,18,39 we found that patients with +8 had a markedly shorter OS in comparison with those who had NK (median survival 26.8 months vs. 47.5 months, p = 0.003). The analysis of Zoe et al included 496 MDS patients with karyotypic abnormalities from the Victorian Cancer Registry and showed that +8 was identified in 93 (18.75%) patients and independently predicted shorter OS in a multivariate analysis (p = 0.024).…”
Section: Discussionsupporting
confidence: 92%
“…6,8,10 The revised international prognosis scoring system (IPSS-R) assigned +8 into the intermediate risk group. 14 However, patients with +8 are prognostically different with median overall survival (OS) from 5.9 to 26 months, [15][16][17] which is partly depending on the racial background. Median OS of patients with sole +8, varying from 32.5 to 85.9 months, are even harder to predict.…”
Section: Introductionmentioning
confidence: 99%
“…However, a Chinese report also indicated an association of isolated trisomy 8 with a much better prognosis, and a median survival of 44 months [29], which was higher than the Western results. A previous study disclosed that a high frequency of myeloproliferative features either at diagnosis or during evolution in MDS with isolated +8, respond poorly to hypomethylating agents (HMAs) [57]. Moreover, patients with isolated trisomy 8 present a high risk of progression to AML [26].…”
Section: Genetic Characteristics Are Concordant With the Prognosis Difference Observed Between Asian And Western Mds Patients 241 Cytogenmentioning
confidence: 99%
“…Although trisomy 8 in MN prognosis has been related to a certain level of mosaicism in the normal population [27,28] and as an isolated alteration does not define the presence of MDS in the lack of other criteria [29], it is also an alteration classified within the intermediate prognosis group for AML and recently as an unfavorable prognosis marker in primary myelofibrosis [30]. Moreover, it has also been reported that in MDS patients presenting myeloproliferative features as well as in CMML patients, carrying trisomy 8 is linked to a worse prognosis [31,32]. Whether proliferation-related alterations have a role in the progression of the disease is something to be studied in the future.…”
Section: Discussionmentioning
confidence: 99%